Bougainvillea spectabilis as a Biological Learning Resource - Muliana GH (PT ARRUS Intelektual Indonesia, 2024)
The background of this research is to identify plants in the surrounding environment that can be utilized as a biological learning resource, specifically Bougainvillea spectabilis or locally known as bougainvillea. Information about the anatomy of plant organs, plant morphology, posture and habitus, up to the roles and benefits of this plant can be used as a source for biology learning. The research method employed is a qualitative type utilizing descriptive analysis techniques with a literature review. Data sources were obtained from journal articles and books discussing the Bougainvillea spectabilis plant. The data collection technique involved three stages: a. Collecting journal articles and books that examine and discuss the Bougainvillea spectabilis plant, b. Organizing information and data obtained through a predetermined framework, c. Further analyzing the organized data using established principles, theories, and methods until the research objectives were achieved. The results of the study indicate that the Bougainvillea spectabilis plant can be used as a biological learning resource for basic biology courses, plant anatomy, plant morphology, higher plant botany, and plant physiology courses.